Ovarian endometrioma: guidelines for selection of cases for surgical treatment or expectant management. (January 2013) - Carnahan, Molly; Fedor, Jennifer; Agarwal, Ashok; Gupta, Sajal
Ovarian endometrioma is a benign, estrogen-dependent cyst found in women of reproductive age. Infertility is associated with ovarian endometriomas; although the exact cause is unknown, oocyte quantity and quality are thought to be affected. The present research aims to analyze current treatment options for women with ovarian endometriomas, discuss the role of fertility preservation before surgical intervention in women with ovarian endometriomas and present guidelines for the selection of cases for surgery or expectant management. This review analyzed the factors of ovarian reserve, cyst laterality, size and location, patient age and prior surgical procedures. Based on these factors, the authors recommend three distinct treatment pathways: reproductive surgery to achieve spontaneous pregnancy following treatment, reproductive surgery to enhance IVF outcomes and expectant management with IVF.